2009
DOI: 10.1007/s00003-009-0531-0
|View full text |Cite
|
Sign up to set email alerts
|

Simplified nutrient labelling: consumers’ perceptions in Germany and Belgium

Abstract: Growing consumer interest in food and health has motivated the European food industry to provide more simple information about the nutritional composition of foods. In addition to the traditional back-of-pack nutrition table, simplified front-of-pack labels have been introduced by the food industry to allow consumers making better informed and healthier food choices. In this study, consumers' perceptions of simplified nutrition information, namely Guideline Daily Amount (GDA) and Traffic light (TL), in Germany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 10 publications
4
60
0
Order By: Relevance
“…As no important difference was found between countries regarding the perceived importance of both qualifying and disqualifying nutrients, provision of information about the same nutrients on food labels across countries is proposed. The labelling format is perhaps more important as suggested by Möser, Hoefkens, Van Camp, and Verbeke (2010) who found that whereas most consumers in Belgium indicated a preference for the GDA, in Germany the TL was favoured most. More important than cross-country differences are the differences in perceived nutrient importance according to the level of health consciousness, age, gender and diet status, which may require a segmentation and targeted information provision.…”
Section: Discussionmentioning
confidence: 91%
“…As no important difference was found between countries regarding the perceived importance of both qualifying and disqualifying nutrients, provision of information about the same nutrients on food labels across countries is proposed. The labelling format is perhaps more important as suggested by Möser, Hoefkens, Van Camp, and Verbeke (2010) who found that whereas most consumers in Belgium indicated a preference for the GDA, in Germany the TL was favoured most. More important than cross-country differences are the differences in perceived nutrient importance according to the level of health consciousness, age, gender and diet status, which may require a segmentation and targeted information provision.…”
Section: Discussionmentioning
confidence: 91%
“…Other dimensions include the choice between qualifying and disqualifying nutrients and the choice for a reference base (e.g., per 100 g/ml/kcal, serving) (Drewnowski, 2007;Verhagen and Van den Berg, 2008;Möser et al, 2010). In general, the various dimensions on which the schemes differ are not independent from each other and combinations of different approaches have been suggested.…”
Section: Dimensions On Which Nutrition Labeling Schemes Differmentioning
confidence: 97%
“…One study recommended that calorie information be presented in a neutral, white box because when it was displayed inside a starburst shape consumers interpreted the attention-grabbing nature of the symbol as an indication that the calorie information was for the whole (20) 9. Mö ser A, Hoefkens C, Van Camp J et al (2010) (21) 10. Levy AS, Mathews O, Stephenson M et al (1985) (22) 11.…”
Section: Consumer Preferences For Label Elements and Systemsmentioning
confidence: 99%